Spectroscopic study of binding of a cationic Pheophorbide-a to an antiparallel quadruplex Tel22 - Ryazanova, O.A.; Zozulya, V.N.; Voloshin, I.M.; Glamazda, A.Yu.; Dubey, I.Ya.; Dubey, L.V.; Karachevtsev, V.A. (Вiopolymers and Cell, 2019)
Aim. To study the binding of a water-soluble cationic Pheophorbide-a derivative (CatPheo-a) ta a Na+–stabilized antiparallel quadruplex formed by 22-mer oligonucleotide d[AG3(T2AG3)3] of the human DNA telomeric sequence (Tel22, PDB ID: 143D). Methods. Absorption and polarized fluorescence spectroscopy were used to determine the properties of DNA–ligand complexes. Fluorescence titration was applied to evaluate the Tel22 dye binding affinity. Absorption melting was used to estimate the effect of CatPheo-a on thermodynamic parameters of the Tel22 quadruplex folding. IR spectroscopy was used to detect singlet oxygen generation . Results. CatPheo-a was found to bind effectively to the Tel22 quadruplex via two competitive binding modes, which are characterized by opposite changes in the dye fluorescence. The spectroscopic properties of CatPheo-a + Tel22 complexes were determined. Thermodynamic parameters of the Tel22 quadruplex folding with/without CatPheo-a were calculated. Conclusions. CatPheo-a destabilizes the quadruplex structure of Tel22 with a two-fold decrease in the equilibrium quadruplex folding constant at 37°C. The efficiency of singlet oxygen generation by CatPheo-a is higher than that by the anionic Pheo-a. Мета. Дослідити зв’язування водорозчинної катіонної похідної Феофорбіду-a (CatPheo-a) з Na+–стабілізованим антипаралельним квадруплексом, утвореним 22-мерним олігонуклеотидом d[AG3(T2AG3)3] теломерної послідовності ДНК людини (Tel22, PDB ID: 143D). Методи. Абсорбційна та поляризована флуоресцентна спектроскопія були застосовані для визначення властивостей комплексів ДНК–ліганд. Флуоресцентне титрування використовували для оцінки аффінності зв’язування барвника з Tel22. Абсорбційне плавлення було застосоване для оцінки впливу CatPheo-a на термодинамічні параметри формування квадруплексу Tel22. ІЧ-спектроскопію використовували для виявлення генерації синглетного кисню. Результати. Встановлено, що CatPheo-a ефективно зв’язується з квадруплексом Tel22 шляхом двох конкуруючих типів зв’язування, які характеризуються протилежними змінами флуоресценції барвника. Визначені спектроскопічні властивості комплексів CatPheo-a + Tel22. Розраховані термодинамічні параметри формування Tel22 квадруплексу з/без CatPheo-a. Висновки. Виявлено, що CatPheo-a дестабілізує структуру квадруплекса Tel22, знижуючи в 2 рази рівноважну константу його утворення при 37°C. Ефективність генерації синглетного кисню CatPheo-a вища, ніж у аніонного Pheo-a. Цель. Изучить связывание водорастворимого катионного производного Феофорбида-a (CatPheo-a) с Na+–стабилизированным антипараллельным квадруплексом, образованным 22-мерным олигонуклеотидом d[AG3(T2AG3)3] теломерной последовательности ДНК человека (Tel22, PDB ID: 143D). Методы. Абсорбционная и поляризованная флуоресцентная спектроскопия были применены для установления свойств комплексов ДНК–лиганд. Флуоресцентное титрование применяли для оценки аффинности связывания красителя с Tel22. Абсорбционное плавление было использовано для оценки влияния CatPheo-a на термодинамические параметры формирования квадруплекса Tel22. ИК-спектроскопию применяли для обнаружения генерации синглетного кислорода. Результаты. Установлено, что CatPheo-a эффективно связывается с квадруплексом Tel22 посредством двух конкурирующих типов связывания, которые характеризуются противоположными изменениями флуоресценции красителя. Определены спектроскопические свойства комплексов CatPheo-a + Tel22. Рассчитаны термодинамические параметры формирования Tel22 квадруплекса с/без CatPheo-a. Выводы. Установлено, что CatPheo-a дестабилизирует структуру квадруплекса Tel22, снижая в 2 раза равновесную константу его образования при 37°C. Эффективность генерации синглетного кислорода CatPheo-a выше, чем у анионного Pheo-a.